Effect of light-sticks and electralume attractors on surface-longline catches of swordfish (Xiphias gladius, Linnaeus, 1959) in the southwest equatorial Atlantic - Hazin, H. G. (2017)
Two experimental fishing trials were carried out off the coast of Pernambuco, Brazil, in 1999 and 2001, using a small artisanal longliner. In experiment 1, six-hook baskets with three chemical light-sticks on alternating hooks had significantly higher catch rates than those with zero or with a light-stick on every hook, with most swordfish accounted for by hooks with light-sticks. Analysis of the data from experiment 2 showed no significant difference between electralume attractors, consisting of AA lithium batteries protected by a solid cover and light-sticks that produce a fluorescent light when two chemical products are mixed. Significant differences were detected in mean CPUE by size class, with most swordfish belonging to class ‘b’ (125–170 cm lower jaw to fork length (LJFL)). No differences, however, were found for swordfish catches in classes ‘a’ (<125 cm LJFL) and ‘b’, and no evidence was found of interaction between the two factors (attractor and size class). Although there was no significant difference between the total length-frequency distributions of swordfish caught with light-sticks and electralume attractors, significant differences were found for fish smaller than 125 cm LJFL, with electralume catches consisting of smaller swordfish than those of gear using light-sticks.